The designer's desktop manual - Simmons, Jason (RotoVision, 2010)
Empowers designers at all levels. This book unravels the essential aspects of key areas of print- and screen-based design. It covers the technical issues and skills needed for a specific area of design. It covers the software updates, tackles common technical problems, and establishes practice guidelines alongside technical hints and tips.